Teaching Comprehension Skills using Context –Based Texts in Second Language Learning at Tertiary Level - Abu Samah, Siti Akmar; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
Content-based reading texts play a vital role in the acquisition of knowledge and information in various fields of studies. Reading these texts at higher institution demands a great deal of effort from the students who are learners of English as a Second Language (ESL). These students who are generally school leavers, whose level or reading exposure is confined to Bahasa Malaysia-based text in their primary and secondary education, have to tackle on their own the tremendous demand of reading and comprehending the English content-based texts. These texts are derived from reference books or lecture notes, which are in English and may pose language barriers for the ESL learners. These are also ESL learners when first enter tertiary level; have met a minimum requirement of at least a credit in English as a second language at secondary school level. These reading materials pose comprehension difficulties when they are streamlined into specific field of studies. This paper attempts to look into the training of selected comprehension skills that language lecturers, particularly new ones in the teaching field, can apply the teaching skills to help learners to alleviate the comprehension challenges when reading content-based texts. This paper is also intended to assist new language lecturers who are embarking in ESL teaching of reading comprehension using content-based texts.